Analisis Efektifitas Sumber Dana Pihak Ketiga Dalam Pemberian Kredit Pada PT. Bank Rakyat Indonesia (BRI) Unit Kangean - Sa'diyah, Halimatus (SUSTAINABLE, 2025)
Bank Rakyat Indonesia (BRI) is a business entity with the task of collecting funds from the community in the form of deposits and rechannelling them back to the community in the form of credit with the aim of improving the standard of living of many people. The purpose of this research determined the level of effectiveness of third-party funding sources in distributing credit to Bank Rakyat Indonesia in Kangean of Sumenep in the period of 2020 - 2023. The method used a qualitative descriptive method with the type of data used that was primary data through interviews, observations and documentation. To measure the effectiveness of third-party funding sources in credit distribution, this research used analysis of Loan Deposit Ratio (LDR). The results based on the calculation of the Loan Deposit Ratio (LDR) in 2020 and 2021 LDR which was achieved in the range of 49% and 55%, meaning that the use of third- party sources of funds in credit distribution was not effectively used. In 2022 and 2023, the LDR reached in the range of 65% and 61% meant that the use of third-party sources of funds in credit distribution had been used very effectively. The use of third-party funding sources in credit distribution for 4 years from 2020 – 2023 LDR which was achieved in the range of 58% meant that the use of third-party funding sources in credit distribution was still ineffective. Since, many funds had not been channelled as a result of the impact of the Covid-19 pandemic and strong competition between banks and high interest rates can reduce public interest in applying for credit.